DESIGN OPTIMIZATION AND TESTING OF 200 AMPS BOOSTER TRANSFORMER BASED ON DIFFERENTIAL EVOLUTION ALGORITHM - Salkoski, Rasim; CHorbev, Ivan (My University, 2020)
Differential Evolution is a population based search algorithm, which is an improved version of Genetic Algorithm. Simulations carried out involved solving optimization problems using Penalty function method. The optimization techniques based Differential Evolution used in the design of the booster transformer result in saving of supply electric energy for the railway power supply systems. Special interest is given to the minimization of production and exploitation costs of the booster transformer. The optimization algorithm based on Differential Evolution is applied to the problem of minimizing the cost of the active parts of the booster transformer. Verification of results is confirmed in an independent accredited laboratory.
Keywords: Differential Evolution Algorithm, Booster Transformer, Optimization techniques, Railway, Temperature rise Test, Impulse Test